THE PRINCIPLE OF FREEDOM OF CONTRACT IN INTERNATIONAL BUSINESS AGREEMENTS - Yasin, Yani Yunisar; Ratnaningsih; Lawado, Irma Sahvitri (JILPR Journal Indonesia Law and Policy Review, 2025)
This study aims to analyze the principle of freedom of contract in international business agreements, focusing on the language to be used in the agreement and applicable laws and regulations. The principle of freedom of contract is one of the basic principles in contract law that allows the parties to make agreements that suit their needs and interests. In international business agreements, the language used can play an important role in determining the meaning and interpretation of the agreement. Differences in language and culture can cause misunderstandings and difficulties in interpreting the agreements made. Therefore, this study will analyze how the use of Indonesian in international business contracts is reviewed from the principle of freedom of contract, as well as how legal reforms related to the use of language in international business contracts are more adaptive. This study uses a normative analysis method with a juridical approach. The results of this study indicate that the principle of freedom of contract in international business agreements allows parties to determine the language used in the agreement, one of which is Indonesian. However, the parties must consider the advantages and disadvantages of using the language and ensure that the use of the language is in accordance with the principle of freedom of contract and applicable laws and regulations. Therefore, it is important to consider the role of language in international business agreements and its implications for global business practices. This study is expected to contribute to the understanding of the principle of freedom of contract in international business agreements and the role of language in agreements. The results of this study can also be used as a reference for legal and business practitioners in making effective and efficient international business agreements.